2016
DOI: 10.1002/ange.201511053
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Conformational Flexibility at Work: Zipping and Unzipping within a Cyclic Peptoid Single Crystal

Abstract: A peptidomimetic compound undergoes a reversible single‐crystal‐to‐single‐crystal transformation upon guest release/uptake with the transformation involving a drastic conformational change. The extensive and reversible alteration in the solid state is connected to the formation of an unprecedented “CH–π zipper” which can reversibly open and close (through the formation of CH–π interactions), thus allowing for guest sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Upon reinjection, the samples equilibrated to provide a mixture of peaks, consistent with multiple slowly-interconverting conformations at room temperature. Several research groups have shown that 6-residue (18-member) macrocycles containing proline exhibit multiple slowly-interconverting conformations at room temperature; [21][22][23] however, these conformations can be biased by internal steric interactions such as a well-placed methyl group 24 or via external sources such as cation-carbonyl interactions. Q-Pro containing macrocycles contain more functional groups than these previously described macrocycles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon reinjection, the samples equilibrated to provide a mixture of peaks, consistent with multiple slowly-interconverting conformations at room temperature. Several research groups have shown that 6-residue (18-member) macrocycles containing proline exhibit multiple slowly-interconverting conformations at room temperature; [21][22][23] however, these conformations can be biased by internal steric interactions such as a well-placed methyl group 24 or via external sources such as cation-carbonyl interactions. Q-Pro containing macrocycles contain more functional groups than these previously described macrocycles.…”
Section: Resultsmentioning
confidence: 99%
“…Several research groups have shown that 6-residue (18-member) macrocycles containing proline exhibit multiple slowly interconverting conformations at room temperature; however, these conformations can be biased by internal steric interactions such as a well-placed methyl group or via external sources such as cation-carbonyl interactions. To test whether QPM could adopt well-defined structures in a solution, we screened multiple metal triflates against QPM- 3 (Figure B).…”
mentioning
confidence: 99%
“…Just as cyclization is known to stabilize folded peptide conformations, [20][21][22][23][24] so have similar strategies been successful at achieving pre-organized spiroligomer 25 and peptoid macrocycles. [26][27][28][29][30][31][32][33][34] Indeed, preorganization due to cyclization helps explain the prevalence of cyclic designs in the modest corpus of peptoid crystal structures that have been solved to date. 1 Interestingly, it has been found that cyclic peptoids can host metal cation adducts through the coordination of backbone carbonyl groups, 31,35 reminiscent of natural products such as mycotoxins.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of solvent molecules is known to be crucial in determining the resulting crystal form. The employment of different crystallization solvents can produce indeed different crystal forms, where the solvent molecules could affect the solid state assembly [4,5]. The effect of the solvent can indeed influence the growth, the morphology and the packing of crystal structures [6][7][8][9][10][11][12][13][14], so that the same ligand can crystallize in different forms [4].…”
Section: Introductionmentioning
confidence: 99%